Answer:
![(3)/(2)](https://img.qammunity.org/2022/formulas/mathematics/high-school/mnscco4nc1evl769d3cq30sp05j8za9ox9.png)
Step-by-step explanation:
First, we need to open the brackets on either side of the equation.
- 4z+4 = 5z-10+1
After opening the brackets, we need to separate the variables from the constants.
-4z-5z = -10+1-4
Then we need to convert the variable fraction into a normal variable by multiplying the variable fraction and also all other terms in the equation.
3(
) 3(-4z) 3(-5z) = 3(-10) + 3(1) + 3(-4)
z -12z -15z = -30+3-12
Now, we can simplify the equation !
-26z = -39
z = -39รท-26
=
![(3)/(2)](https://img.qammunity.org/2022/formulas/mathematics/high-school/mnscco4nc1evl769d3cq30sp05j8za9ox9.png)